Reading Instruction in Science for Students With Learning Disabilities: A Meta-Analysis. (August 2015) - Kaldenberg, Erica R.; Watt, Sarah J.; Therrien, William J.
As a growing number of students with learning disabilities (LD) receive science instruction in general education settings, students with LD continue to perform significantly lower than their non-disabled peers. The shift from textbook-driven instruction to inquiry-based approaches to science learning supports students who struggle with reading. However, research continues to show that for students to fully access the science curriculum, it is critical to address effective ways to increase reading comprehension of expository science text. This meta-analysis identified 20 studies from 12 articles that evaluated the efficacy of such interventions. Effect sizes were calculated for each study. Across all studies, a mean effect size (ES) of 0.98 was obtained. Findings align with past research on reading comprehension of expository text indicating that students with LD benefit from explicit vocabulary instruction (ES = 1.25) and the use of multicomponent interventions (ES = 0.64) when reading science-related material.